Intentions and Behavior of the Youth to Work in the Agricultural Sector - Likin Ruhkmauddin; Nuhfil Hanani; Fitria Dina Riana (The University of Lampung, 2025)
The agricultural sector in Indonesia holds significant business potential, contributing 9.82% to GDP from 2018 to 2021. Despite its importance, this sector faces challenges such as high business risks, social inequalities, and a lack of young farmer regeneration. This study aims to analyze the influence of attitudes, subjective norms, and perceived behavioral control on the intentions and behaviors of young people working in agriculture. The study was conducted in Kliteh Village, Malo District, Bojonegoro Regency, with 100 respondents aged 17-35 years. The method used was a survey with a simple random sampling technique and data analysis using Structural Equation Modeling-Partial Least Square. Findings indicate that attitudes, subjective norms, and perceived behavioral control positively and significantly influence of intention and behavior of young people to working in agriculture. Additionally, intentions also positively and significantly influence behaviors of young people in the agricultural sector. This research highlights the importance of supporting positive attitudes, social norms, and perceived behavioral control to enhance participation of young people participation in agricultural sector. Keywords: Agricultural Sector, Behavior, Intent, SEM-PLS, Young Generation.